The Dynamics of CD4+ T Cell Proliferation in Autopilot Model (CSIAM Transactions on Life Sciences, 2026)
Under the assumption of the autopilot model, after antigen stimulation exceeds a threshold, the proliferation and effector function of CD4+ T cells are self-sustained and do not need further antigen stimulation. However, CD4+ T cell proliferation is driven by their production of IL-2, which then binds to cells and triggers proliferation. Without regulation, this autocrine process forms a positive feedback loop that causes uncontrolled proliferation. This study mathematically modeled the regulatory mechanisms of the CD4+ T cell response after infection, focusing on the role of IL-2 self-regulation and Treg in this mechanism. We performed a phase-space analysis to study the long-term behavior of the proliferation process. Our results show that IL-2 self-regulation alone is not sufficient to fully inhibit CD4+ T cell response, and that the involvement of Treg cells is essential to regulate the immune response effectively. In particular, when the rate of CD4+ T cell proliferation is controlled by the rate of IL-2-mediated CD4+ T cell removal, Treg cells control CD4+ T cell proliferation by releasing immunosuppressive cytokines such as IL-10 and TGF-$β$, thus inhibiting the unregulated immune response.
Keywords: Adaptive immune system; immune response; within-host; clonal expansion